Quantitative Trade Controls/ Trade Relations Between Free—Market and Controlled Economies (Book). - Hickman, C. Addison (The Accounting Review, 1944)
Abstract Reviews two books on trade. "Quantitative Trade Controls: Their Causes and Nature," by Gottfried Haberler and Martin Hill; "Trade Relations Between Free-Market and Controlled Economies," by Jacob Viner.